ANTIMICROBIAL AND ANTI – INFLAMMATORY ACTIVITIES OF EXTRACTS OF FICUS THONNINGII BLUME (MORACEAE) (2014)
Infectious diseases and the associated inflammation pose a serious health problem worldwide, accounting for about 50% of all deaths in tropical countries. This is further complicated by the frequent development of bacterial resistance to many chemotherapeutic agents. These problems have necessitated the continuous search for new and effective drugs from plant materials. Thus, Ficus thonningii Blume (Moraceae), a plant used ethnomedicinally in West Africa for the treatment of some microbial infections, was studied for its antimicrobial and anti-inflammatory activities. Dried leaves and stem bark of Ficus thonningii were screened for secondary metabolites. Successive gradient extraction was carried out on the pulverised plant parts using hexane, chloroform and methanol with Soxhlet apparatus. Antimicrobial activity of the extracts on Gram-positive (10) and Gram-negative (11) bacteria, and fungal (12) isolates was evaluated using agar-diffusion method. Antibiogram of the microorganisms was determined using established antibiotics. Bioassay-guided fractionation of crude extracts using column chromatography was done. Minimum Inhibitory Concentrations (MIC) and minimum bactericidal concentrations of the crude extracts, fractions and isolated compound were determined by agar-dilution. Bactericidal kinetics of the methanol leaf extract against Staphylococcus aureus and Escherichia coli at 2.5-10.0 mg/mL were determined. Structure elucidation of the bioactive compound was carried out using 1H-NMR, 13C-NMR, DEPT 135, COSY, UV and GC-MS spectroscopy. In vivo anti-inflammatory activity of leaf extract was evaluated using carrageenan-induced rat paw oedema with acetylsalicylic acid as the reference drug. Acute oral toxicity, haematological and histopathological evaluations were carried out to determine the safety profile of methanol leaf extract in rats. Statistical analysis was carried out using Student’s t-test at p = 0.05. Alkaloids, flavonoids, terpenoids and cardiac glycosides were detected in the plant extracts. Antimicrobial assay of crude extracts and fractions showed a broad spectrum activity on sensitive and multidrug-resistant strains with the leaf and stem bark extracts having similar antimicrobial activity. Hexane leaf extract and bioactive fractions gave MIC range of 78-625 µg/mL and 20-625 µg/mL respectively while methanol leaf extract and bioactive fractions gave 156-625 µg/mL and 39-625 µg/mL. Structure elucidation of the bioactive compound isolated from hexane leaf fraction revealed a triterpenoid with MIC range of 20-156 µg/mL (Gram-positive bacteria), 39-156 µg/mL (Gram-negative bacteria) and 10-78 µg/mL (fungi), while that of gentamicin and tioconazole were 5-30 µg/mL and 10-20 µg/mL respectively. Methanol leaf extract showed bactericidal activity in a concentration-dependent manner on the microorganisms, with a 100% bactericidal action at 10 mg/mL on Staphylococcus aureus and 84% on Escherichia coli within 4 hours. The anti-inflammatory activity of methanol leaf extract was 57.5% while that of acetylsalicylic acid was 93.2%. Acute oral toxicity of methanol leaf extract showed an LD50> 5g/Kg. Significant increases were observed in the red blood cell count and mean corpuscular haemoglobin value, while histopathological evaluation revealed no significant tissue pathological changes in the major organs. Extracts of Ficus thonningii leaves contain antimicrobial and anti-inflammatory agents. These could be useful in the development of safe chemotherapeutic agents for the treatment of relevant microbial infections and inflammation-prone diseases.